Assessment of acculturation in Deadwood South Dakota's Chinese community from 1877-1930 - DeBack, Shane Phillip (My University, 2010)
This thesis takes a look at the notion of acculturation and the extent to which it was taking place in the Chinese community of Deadwood South Dakota from 1877-1930. I have used as a primary source the Deadwood Chinatown report as well as historic books written on the subject. This thesis presents the findings from my archaeological investigation into the Chinese community of Deadwood and the methodology used to come up with my results. By all indications the Chinese community of Deadwood South Dakota was able to maintain their own culture identity while at the same time embracing their new American way of life. The Chinese community was a strong presence in Deadwood and became a significant influence in the towns? development and history.
Keywords: Chinese Americans -- South Dakota -- Deadwood.; Chinese Americans -- Black Hills (S.D. Wyo.) -- Antiquities.; Chinese Americans -- Black Hills (S.D. Wyo.) -- History.